Forecasting of Corrosion Properties of Steel Wires for Production of Guide Wires for Cardiological Treatment - J. Przondziono; W. Walke; E. Hadasik; R. Młynarski (Advances in Materials Science and Engineering)
The study presents evaluation of the influence of strain in drawing process and of surface modification on resistance to electrochemical corrosion of wires made of stainless steel for production of guide wires used in invasive cardiology. The results of static tensile test enabled us to determine the course of flow curve of wires made of X10CrNi 18-8 steel as well as mathematical form of flow stress function. Resistance to electrochemical corrosion was evaluated on the ground of registered anodic polarisation curves by means of potentiodynamic method. The tests were performed in solution simulating human blood on samples that were electrolytically polished and samples that were polished and then chemically passivated. Exemplary anodic polarisation curves were given. It was proved that with the applied strain, corrosion properties decrease. It was found that chemical passivation improves wire corrosion characteristics. Statistical analysis showed that there is a significant dependence between corrosion properties (polarisation resistance Rp) and strain ε applied in drawing process. Functions that present the change Rp=f(ε) were selected. The issue is of importance to guide wire manufacturers because application of the suggested methodology will enable us to forecast corrosion characteristics of wire with the required strength drawn with the applied strain.